Impact of Forced Marriage on Young Women in Bades Village, Pasirian, Lumajang - Ainiyah, Qurrotul; Nisah, Yulia (Pusat Studi Aswaja An-Nahdliyyah UNISNU Jepara, 2025)
Forced marriage has been identified as one of the primary causes of marital failure. This study aims to delve into the social, cultural, and economic factors that drive the practice of forced marriage in the Bades community. Employing a case study approach, this research reveals the following: Firstly, the tradition of arranged marriages without the consent of the child is common among the mountainous people of Bades, leading to the stigmatization of unmarried women over the age of 18 as